The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-3148.2009.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of Flebogammadif®, a new high‐purity human intravenous immunoglobulin, in adult patients with chronic idiopathic thrombocytopenic purpura

Abstract: Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disorder characterized by a low platelet count and bleeding, whose incidence is approximately 6.2 for each 100,000 adults per year. Intravenous immunoglobulins (IVIG) can be useful in patients with ITP to prevent bleeding or prior to surgery. In this study, the efficacy and safety of Flebogammadif, a new high-purity IVIG, were assessed by an open, multicentre, non-controlled, prospective study in adult patients with chronic ITP. A total of 20 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
12
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
7
12
1
Order By: Relevance
“…This is consistent with what can be observed when comparing clinical trials with these products (Berger ; Ballow ; Julia et al. ; Berger et al. ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with what can be observed when comparing clinical trials with these products (Berger ; Ballow ; Julia et al. ; Berger et al. ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous data from clinical trials performed with Flebogamma DIF at 10% and 5% concentrations showed a frequency of infusions with potentially related AEs, relative to the number of infusions, of 30.5% and 10.8%, respectively (Berger 2007;Ballow 2009;Julia et al 2009;Berger et al 2010). Therefore, to ensure more than 90% power using a one-sided test with a significance level of 0.01, an effective sample size of at least 102 infusions per group was needed to detect a difference of 20% in the rates of both concentrations (sample size for the comparison of two independent proportions with Z test).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations